2018
DOI: 10.2215/cjn.04690417
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Transplantation Referral Ratio to Assess Performance of Transplant Referral among Dialysis Facilities

Abstract: Background and objectives For patients with ESRD, referral from a dialysis facility to a transplant center for evaluation is an important step toward kidney transplantation. However, a standardized measure for assessing clinical performance of dialysis facilities transplant access is lacking. We describe methodology for a new dialysis facility measure: the Standardized Transplantation Referral Ratio.Design, setting, participants, & measurements Transplant referral data from 8308 patients with incident ESRD wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
2
18
0
1
Order By: Relevance
“…In fact, policy changes since 2015, such as addition of calcimimetics into the bundled PPS, may further affect practice and practice variation. Facility variation is common in hemodialysis care and has been reported in anemia management, dialysis access, timing of dialysis initiation, and kidney transplant referrals (19)(20)(21)(22). Our findings are generally consistent with results from the Dialysis Outcomes and Practice Patterns Study (DOPPS) that demonstrated substantial facility variation in cinacalcet use for mineral metabolism management (23).…”
Section: Discussionsupporting
confidence: 83%
“…In fact, policy changes since 2015, such as addition of calcimimetics into the bundled PPS, may further affect practice and practice variation. Facility variation is common in hemodialysis care and has been reported in anemia management, dialysis access, timing of dialysis initiation, and kidney transplant referrals (19)(20)(21)(22). Our findings are generally consistent with results from the Dialysis Outcomes and Practice Patterns Study (DOPPS) that demonstrated substantial facility variation in cinacalcet use for mineral metabolism management (23).…”
Section: Discussionsupporting
confidence: 83%
“…Transplant center organization and practice may influence transplantation activity. To the best of our knowledge, studies about the center effect in the field of transplantation focused on the role of dialysis facility characteristics on access to the waiting list, and the outcome on transplantation .…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that kidney transplant recipients would be more effective as navigators, because they have already completed the steps in the transplant process. Other efforts to increase access to kidney transplantation include educating patients on dialysis about the option of transplantation, developing measures of transplant referral, streamlining the transplant workup, communicating with potential living donors, and disseminating data on rates of transplantation (15,(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%